2020
DOI: 10.38094/jocef1110
|View full text |Cite
|
Sign up to set email alerts
|

University Students' Attitudes Towards Animal Welfare in Duhok Zoo

Abstract: Here in Kurdistan Region of Iraq, particularly in Duhok zoo, animal welfare is mostly neglected. Animals are not treated normally. As far as the author is aware, there is no study undertaken to understand the students or public attitudes toward animals in Duhok zoo. Therefore, the purpose of this study was to investigate the attitudes of the students of the University of Zakho, Faculty of Sciences, Departments of Environmental Sciences, and Biology about animal welfare concerns of Duhok Zoo. The study was unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Perceptions of good health were evident when animals appeared “ well groomed ” [16], as this signified that animals “ were respected ” [48]. Additionally, signs of a healthy weight were viewed positively [16], but negative perceptions arose when animals were perceived to show signs of injury or disease, appeared in poor physical condition, or were under or overweight [16, 19, 29, 54, 59, 64]. Indeed, expectations for robust health may override other expectations: for example, animals may have large, naturalistic enclosures with ample enrichment, but if they appear to be injured or unwell, perceived poor health status may be an overriding factor [115].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Perceptions of good health were evident when animals appeared “ well groomed ” [16], as this signified that animals “ were respected ” [48]. Additionally, signs of a healthy weight were viewed positively [16], but negative perceptions arose when animals were perceived to show signs of injury or disease, appeared in poor physical condition, or were under or overweight [16, 19, 29, 54, 59, 64]. Indeed, expectations for robust health may override other expectations: for example, animals may have large, naturalistic enclosures with ample enrichment, but if they appear to be injured or unwell, perceived poor health status may be an overriding factor [115].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies found that behaviours which visitors perceived to be active and natural were considered positive indicators of welfare [10,16,19,35,38,41,43,46,52,54,59,62,70,77,88,[94][95][96][97][98][99][100][101][102][103][104][105]. In contrast, behaviours perceived as abnormal or inactive were thought to be negative indicators [2,16,19,38,40,41,47,61,64,71,73,95,99,104,[106][107][108].…”
Section: Animal Behaviourmentioning
confidence: 99%
See 2 more Smart Citations